Electrodeposition and characterization of Cu2S thin films from aqueous solution - Anuar, K.; Zainal, Z.; Hussein, M. Z.; Ismail, H. (2001)
An electrodeposition method was used to prepare Cu2S thin film deposited on Ti substrate. The effect of deposition potential, concentration and deposition time was studied to determine the optimum condition for the electrodeposition process. Cyclic voltammetry was performed to elucidate the electrodic processes that occur while potentials for electrodeposition were applied to determine the optimum potential for electrodeposition. The thin films were characterized by X-ray diffractometry. Scanning electron microscopy was performed to observe the morphology, composition and structure of the deposits. Cu2S showed a cubic morphology.